Analysis Of Government Sourcing Health Financing With District Health Account (DHA) Approach In Deli Serdang Regency, 2018-2020 - Novita Haryani; Sri Wahyuni Nasution; Chrismis Novalinda Ginting (CV. Inara, 2022)
Improving the health status of a community according to the World Health Organization (WHO) requires a minimum budget of 5% - 6% of the total state budget of a country, while to achieve the ideal health status a budget of 15% - 20% of the state budget is needed. A large enough budget is needed because health costs are quite high, while health must still be a priority because it is an investment to improve the health and productivity of its citizens. The District Health Account is a systematic, comprehensive and consistent way of monitoring the flow of funds/financing to the health system in a district/city. The purpose of this study was to analyze government-sourced health financing with a district health account (DHA) approach in Deli Serdang Regency in 2018-2020. This type of research is a quantitative study with a crosssectional design. Sampling technique The sampling technique in this study was the total population, that is, the entire population was used as the research sample. The results of the study explain that the source of health costs, health financing budget managers, health financing service providers, types of health financing activities, health financing budget items, types of health financing programs. levels of government-sourced health financing programs and beneficiaries of government-sourced health financing in Deli Serdang Regency in 2018-2020 all went well. types of health financing activities, health financing budget items, types of health financing programs. levels of governmentsourced health financing programs and beneficiaries of government-sourced health financing in Deli Serdang Regency in 2018-2020 all went well. types of health financing activities, health financing budget items, types of health financing programs. levels of government-sourced health financing programs and beneficiaries of government-sourced health financing in Deli Serdang Regency in 2018-2020 all went well.